Building a resilient and sustainable food system in a changing world – A case for climate-smart and nutrient dense crops - Mustafa, Maysoun A.; Mabhaudhi, Tafadzwanashe; Massawe, Festo (Elsevier Ltd, 2020)
Current food production and consumption practices have had negative impacts on the environment and are central to global health concerns. Using a mixed-methods review, we examined the nutritional and environmental impacts of our global food systems and addressed the apparent decrease in food sources and crop diversity, and its implication on sustainable and healthy diets. Moreover, we explored the merits of weighing the use of natural capital and agricultural inputs against the output generated in terms of nutrient density. Transforming our food systems to safeguard planetary health will require a shift towards sufficient production of nutrient dense crops that are environmentally sustainable. Such a transformation largely depends on valuing crops for their natural nutrient density and matching them to suitable environments.